Awareness About Viral Infections and Its Prevention Among Public After Covid-19 Pandemic - CHARAN, L.SAI; GEETHA, R.V.; PRIYA, V. VISHNU (The journal of contemporary issues in business and government, 2020)
Information on awareness of public towards viral infections, it’s coverage in general public, prevention of viral infection is like Covid-19 is the major challenge for every country and it formed the basis of healthcare forces. Therefore, it is important to assess the attitude and awareness towards viral infections after Covid-19 pandemic, for the further health policies implementation as well as taking safety measures and following the guidelines. The study objective was to assess the awareness about viral infections and its prevention among the public after Covid-19 pandemic, from the various places of the country. Study was carried out by using multiple-choice structured questionnaires among 119 attendees. The questionnaire was prepared in such a way as to assess the knowledge of the public towards the infection, transmission, screening and prevention of viral infections. The data was collected and it analyses statistically.Although most of the attendants were aware of the existence of COVID-19 and the many other viral infections, the level of awareness regarding prevention, transmission and following the safety guidelines was found to be dissatisfactory. Direct correlation was found between educational level and awareness, which reversed the fact that the attendants with better knowledge and information had better attitudes towards the infection and prevention of COVID-19. Within the limitations of the study, the moderate level of awareness about viral infections and prevention after COVID-19 pandemic is observed